Vigilante Publics: Orientalism, Modernity and Hindutva Fascism in India - Banaji, Shakuntala (Javnost-The Public, 2018)
This paper explores the interconnections of Hindutva fascist repertoires in India and quasi-orientalist discourses. History and common sense are re-written through audiovisual communications to appeal to one section of a dangerously split Indian public and a neoliberal-touristic sensibility elsewhere. Enlightenment rhetorics of progress, democracy and technological development are apparently embodied by WhatsApp groups, electronic voting machines and laws to protect cows. Voting—as a marker of democratic citizenship—becomes a masquerade protecting a resurgent far right Hindutva (Hindu fascist) regime under the aegis of Narendra Modi and the BJP. Caste Hinduism’s association of cows with deities, and the proscription on meat-eating in certain versions of religious practice, are used as pretexts for unimaginable violence against Muslims, Christians, Dalits, and working class/lower caste Hindus. Violence against those who dissent is rationalised as patriotic. Hindutva’s banal and spectacular audiovisual discourse overwhelms public communication. Its consequences are a form of vigilante citizenship that is marked on the bodies of dead victims and of vigilante publics ready to be mobilised either in ethno-cultural violence or its defence and disavowal. Meanwhile, attracted to India as an enormous market, Western governments and corporations have colluded with the Hindutva regime’s self-promotion as a bastion of development.